Photostable and Biocompatible Fluorescent Silicon Nanoparticles for Imaging-Guided Co-Delivery of siRNA and Doxorubicin to Drug-Resistant Cancer Cells - Guo, Daoxia; Ji, Xiaoyuan; Peng, Fei; Zhang, Yiling; Chu, Binbin; Su, Yuanyuan; He, Yao (Nano-Micro Letters, 2019)
The development of effective and safe vehicles to deliver small interfering RNA (siRNA) and chemotherapeutics remains a major challenge in RNA interference-based combination therapy with chemotherapeutics, which has emerged as a powerful platform to treat drug-resistant cancer cells. Herein, we describe the development of novel all-in-one fluorescent silicon nanoparticles (SiNPs)-based nanomedicine platform for imaging-guided co-delivery of siRNA and doxorubicin (DOX). This approach enhanced therapeutic efficacy in multidrug-resistant breast cancer cells (i.e., MCF-7/ADR cells). Typically, the SiNP-based nanocarriers enhanced the stability of siRNA in a biological environment (i.e., medium or RNase A) and imparted the responsive release behavior of siRNA, resulting in approximately 80% down-regulation of P-glycoprotein expression. Co-delivery of P-glycoprotein siRNA and DOX led to > 35-fold decrease in the half maximal inhibitory concentration of DOX in comparison with free DOX, indicating the pronounced therapeutic efficiency of the resultant nanocomposites for drug-resistant breast cancer cells. The intracellular time-dependent release behaviors of siRNA and DOX were revealed through tracking the strong and stable fluorescence of SiNPs. These data provide valuable information for designing effective RNA interference-based co-delivery carriers. Highlights: 1 A novel all-in-one fluorescent nanomedicine platform based on silicon nanoparticles (SiNPs) was developed for imaging-guided co-delivery of short interfering RNA (siRNA) and doxorubicin (DOX). 2 The intracellular time-dependent release behaviors of siRNA and DOX were visually monitored by tracking the strong and stable fluorescence of SiNPs. 3 The SiNPs-based nanocarriers displayed pronounced therapeutic efficiency on drug-resistant breast cancer cells.